2012
DOI: 10.1002/clc.22073
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Enhanced External Counterpulsation as a Treatment for Angina in Patients With Aortic Stenosis

Abstract: Background: Comorbid aortic stenosis (AS) has been considered a precaution when applying enhanced external counterpulsation (EECP) to individuals with angina due to concerns about treatment-related hemodynamic changes. Hypothesis: The aim of this study was to determine whether EECP safely reduces symptoms of myocardial ischemia and improves hemodynamics in individuals with AS. Methods: Forty-three patients with AS (average age, 73 years; 86% male) and 43 comparison patients without AS were chosen from a databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The mean age of patients was 27.1 years in the Gurovich study 15 and 76.8 years in the Braverman study. 16 All studies were published between 1999 and 2020. The evaluation of these studies quality, showed that, sixteen studies out of 17 studies submitted were of high quality and only one article was of low quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of patients was 27.1 years in the Gurovich study 15 and 76.8 years in the Braverman study. 16 All studies were published between 1999 and 2020. The evaluation of these studies quality, showed that, sixteen studies out of 17 studies submitted were of high quality and only one article was of low quality.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 16,[18][19][20]23,24,28 including 291 patients assessed the Barchial Systolic Blood Pressure outcomes of the patients. The overall Inverse Variance Pooled MD calculated for Barchial SBP was 8.83 (95% CI; 7.34, 10.33) in favor of the post-EECP (P < 0.00001, Figure 3A).…”
Section: Effectiveness Systolic Blood Pressure (Sbp)mentioning
confidence: 99%
“…Lin et al [ 16 ] reported that EECP was able to improve the mean blood pressure and cerebral perfusion in patients after ischemic stroke. Another study concluded that angina patients with aortic stenosis who underwent EECP had clinically important symptomatic and hemodynamic improvements comparable to their non-aortic stenosis counterparts [ 17 ]. Ruangkanchanasetr et al [ 4 ] even demonstrated that EECP could improve the long-term renal function in cardiac patients especially in cases with declined renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced external counterpulsation is FDA approved for angina in the United States. [39][40][41][42][43][44][45][46][47] Transmyocardial Revascularization…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%